Aspectos de la religiosidad porteña. Valparaíso, 1830-1930 - Millar Carvacho, René (Historia, 2000)
Valparaiso was the fastest growing town in Chile during the 19th century, to the extent that the original inhabitants became a rninority in relation to the newcomers. The most important of these groups of immigrants were the foreign communities, oil account of their economic and social influence. They left their mark not only in the daily life of the port but also in their wy of thinking and religious attitudes. Valparaiso, in contrast to the rest of Chile, had an important group of noncatholics. The development and public manifestations of these dissidents, was due both to the growth in their numbers and to the weakness of the Catholic presence in that por during the first half of the 19th century. However, from the 1860s on, the situation tended to change due to difficulties faced by the protestants and freemasons, and the recovery of the Catholic Church under the apostolic governor Mariano Casanova. At the end of the century, Catholic worship who had remained aloof from the native population, began to make strong inroads in the midst thanks to the work of the Pentecostalists.